Sialylated keratan sulfate proteoglycans are Siglec-8 ligands in human airways. (17th July 2018) - Gonzalez-Gil, Anabel; Porell, Ryan N; Fernandes, Steve M; Wei, Yadong; Yu, Huifeng; Carroll, Daniela J; McBride, Ryan; Paulson, James C; Tiemeyer, Michael; Aoki, Kazuhiro; Bochner, Bruce S; Schnaar, Ronald L
Abstract: Human siglecs are a family of 14 sialic acid-binding proteins, most of which are expressed on subsets of immune cells where they regulate immune responses. Siglec-8 is expressed selectively on human allergic inflammatory cells—primarily eosinophils and mast cells—where engagement causes eosinophil apoptosis and inhibits mast cell mediator release. Evidence supports a model in which human eosinophils and mast cells bind to Siglec-8 sialoglycan ligands on inflammatory target tissues to resolve allergic inflammation and limit tissue damage. To identify Siglec-8-binding sialoglycans from human airways, proteins extracted from postmortem human trachea were resolved by size-exclusion chromatography and composite agarose–acrylamide gel electrophoresis, blotted and probed by Siglec-8-Fc blot overlay. Three size classes of Siglec-8 ligands were identified: 250 kDa, 600 kDa and 1 MDa, each of which was purified by affinity chromatography using a recombinant pentameric form of Siglec-8. Proteomic mass spectrometry identified all size classes as the proteoglycan aggrecan, a finding validated by immunoblotting. Glycan array studies demonstrated Siglec-8 binding to synthetic glycans with a terminal Neu5Acα2-3(6-sulfo)-Gal determinant, a quantitatively minor terminus on keratan sulfate (KS) chains of aggrecan. Treating human tracheal extracts with sialidase or keratanase eliminated Siglec-8 binding, indicating sialylated KS chains as Siglec-8-binding determinants. Treating human tracheal histological sections with keratanase also completely eliminated the binding of Siglec-8-Fc. Finally, Siglec-8 ligand purified from human trachea extracts induced increased apoptosis of freshly isolated human eosinophils in vitro. We conclude that sialylated KS proteoglycans are endogenous human airway ligands that bind Siglec-8 and may regulate allergic inflammation.